A comparative study between muscle, cartilage and swab from inside the urinary bladder samples for DNA typing of severely burnt bodies in disaster victim identification (DVI). (December 2015) - Ferreira, Samuel T.G.; Paula, Karla A.; Nogueira, Ricardo F.; Oliveira, Elvis S.; Moraes, Adriana V.
Abstract: In mass fatality incidents, the kind and quality of samples collected for DNA typing play an important role in the identification of the victims. Depending on the kind of event and on the conditions of the bodies, it is very important to consider all kinds of possible samples available for DNA typing. In this study, we compared DNA yields and STRs profiles obtained from samples of deep red muscle and cartilage from hip joint (head of femur) and swab from inside the urinary bladder collected from three severely burnt bodies due to a car crash in Brazil. The amount of DNA recovered from each sample and the quality of the STRs profiles obtained demonstrated that deep red muscle, cartilage and swab from inside the urinary bladder are excellent sources of samples for DNA typing of severely burnt bodies in disaster victim identification (DVI).